2021
DOI: 10.31083/j.rcm2202038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical overview of diabetes mellitus as a risk factor for cardiovascular death

Abstract: Global diabetes mellitus prevalence is increasing. Metabolic disorders, such as type 2 diabetes, are associated with abnormal cardiac electrophysiology and increased risk of arrhythmias. Patients with both diabetes types (1 and 2) su fer from sudden cardac death (SCD) as a leading cause of mortality. Cardiovascular death is defined as death attributable to cardiovascular disease (CVD) occurring shortly within the symptom onset. This usually arises from life-threatening ventricular tachyarrhythmias that lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 95 publications
(132 reference statements)
0
12
0
Order By: Relevance
“…Diabetes is a traditional risk factor for CV disease, carrying a higher risk for sudden cardiac death, accelerated atherosclerosis, ischaemic heart disease, cardiomyopathy, and HF [ 35 ]. In addition, oscillating glucose is considered to have more deleterious effects than constant high glucose levels on endothelial function [ 36 ] and postprandial glycaemic spikes may be a more robust determinant of CV disease risk than average glucose levels [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is a traditional risk factor for CV disease, carrying a higher risk for sudden cardiac death, accelerated atherosclerosis, ischaemic heart disease, cardiomyopathy, and HF [ 35 ]. In addition, oscillating glucose is considered to have more deleterious effects than constant high glucose levels on endothelial function [ 36 ] and postprandial glycaemic spikes may be a more robust determinant of CV disease risk than average glucose levels [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a doubtful reduction of coronary artery disease by glucose-lowering treatment was found in large meta-analyses [ 39 , 40 ], possibly because the benefits were partly counterweighed by an increased occurrence of severe hypoglycaemic episodes, associated with the intensive insulin therapy. In fact, hypoglycaemia can be associated with the development of adverse CV outcomes by means of several mechanisms, including blood coagulation abnormalities, inflammation, endothelial dysfunction, and sympathetic responses [ 35 , 41 ]. Accordingly, the panel agreed that CGM with the new glucometrics may have a prognostic role in patients with ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a traditional risk factor for CV disease, carrying a higher risk for sudden cardiac death, accelerated atherosclerosis, ischaemic heart disease, cardiomyopathy, and HF (35). In addition, oscillating glucose is considered to have more deleterious effects than constant high glucose levels on endothelial function (36) and postprandial glycaemic spikes may be a more robust determinant of CV disease risk than average glucose levels (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, a doubtful reduction of coronary artery disease by glucose-lowering treatment was found in large meta-analyses (39,40), possibly because the bene ts were partly counterweighed by an increased occurrence of severe hypoglycaemic episodes, associated with the intensive insulin therapy. In fact, hypoglycaemia can be associated with the development of adverse CV outcomes by means of several mechanisms, including blood coagulation abnormalities, in ammation, endothelial dysfunction, and sympathetic responses (35,41). Accordingly, the panel agreed that CGM with the new glucometrics may have a prognostic role in patients with ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the critical level of D-D is set below 0.5 ÎĽg/mL that could be used as an indicator for eliminating the probability of deep vein thrombosis (Von Känel and Dimsdale, 2003). It has been reported that diabetes mellitus patients present increases of prothrombin activators and thrombinantithrombin complex and a decrease in anti-thrombin, resulting in the clotting balance inclining to the side of thrombogenesis (Abuelgasim et al, 2021).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%